Sociocultural Game-Based Interactive Digital Simulations: A Pathway to Improving Primary School Students' Word Problem-Solving Skills. - Arifin, Slamet; Atmoko, Adi; Zainuddin, Zamzami; Widiyanti (Pertanika Journal of Social Sciences & Humanities, 2026)
In this study, we explore the implementation of a sociocultural game-based interactive digital simulation titled The Adventure of Adit in the Fruit Store game in mathematics learning. The microgenetic method was applied to examine the dynamic changes in students' word problemsolving (WPS) abilities. A total of 140 first-grade students, comprising 57 boys and 83 girls with an average age of 6 to 7 years, participated in six mathematics sessions. We collaborated with the classroom teacher to design a mathematics lesson using the game we designed to teach number addition (1-10). A pre-test and six assessments were administered to students after they engaged with the mathematics learning design. Descriptive statistics were used to analyse the dynamic changes in students' WPS abilities over time, and the Wilcoxon Signed Ranks Test was conducted to compare students' WPS abilities before and after participation in mathematics learning through the game. Our findings demonstrate significant dynamic improvements in students' WPS abilities following participation in the designed mathematics lesson. Moreover, statistical analysis revealed a significant improvement in students' post-test scores compared to pre-test scores, Z = -10.380, p < .001, indicating that the gamebased learning intervention had a substantial effect on enhancing students' word problemsolving skills.